Kemandirian dan Kemerdekaan Kekuasaan Kehakiman - Muhammad Akbar (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The freedom of judges based on the independence of judicial power in Indonesia is guaranteed in the constitution of Indonesia, namely the Constitution of the Republic of I1945, which is further implemented in Law No. 48 of 2009 on the Judicial Power Law. In essence, the duties of judges in law enforcement, particularly in re-enforcing laws that have been violated by the parties or suspects / defendants may proceed well and smoothly if the spirit of the violated legislation reflects a sense of justice in society. Or in other words, that the task of the judge in enforcing the law will not encounter significant obstacles if the existing legislation conforms to the feelings of law and the values of justice that live and thrive in society. Conversely, if the legislations that have been violated are no longer relevant to reality in society, the judge will have difficulty in reestablishing them. If the judge imposes himself to apply the rule to concrete events, it is likely that the creation of injustice Independence shall be construed as free from the influence of the executive or any other State Power and freedom from coercion, directive or recommendation coming from extra judicially parties except in Matters permitted by law.